Kelantan batik: what makes it a preferred product? / Nur Atiqah Zakiyyah Ramlee ...[et al.] - Ramlee, Nur Atiqah Zakiyyah; Wan Omar, Wan Marhaini; Ramli, Nur Haslina; Mohammad, Siti Nur Farzana (Universiti Teknologi MARA Shah Alam, 2020)
Recently, batik has transformed into a new modern style that brings new attraction and fabulous design to people in Malaysia as well as at international level. This kind of transformation has changed the traditional methods of producing batik into new and modern ways that bear the current lifestyle. The emergence of digital printed imitate batik in the batik industry has provided an alternative selection over original batik to customers. This digital printed imitate batik has allowed counterfeiting activities in batik industry specifically for Kelantan batik product. For that reason, this study aims to identify the factors that influence customer preferences in purchasing Kelantan Batik. A questionnaire based survey was used as data collection method and a total of 151 usable questionnaires were collected to confirm the underlying constructs empirically. Data were analyzed to obtain descriptive statistics, to compare mean analysis and to conduct regression analysis for test of relationship. The results suggested that quality becomes a prominent variable when it comes to customers purchasing Kelantan Batik, followed by brand image. The findings of this study may assist Kelantan batik entrepreneurs to identify areas for improvement especially in formulating the future marketing strategies.